Differences in memory and executive functions in children with different level of reading of Huancavelica and Lima - Callao - Canales Gabriel, Ricardo (2020)
The study sought to determine if there are differences in working memory and executive neuropsychological functions in children with different reading levels belonging to different socio-cultural realities. The sample was 71 students from Huancavelica and 82 students from Lima and Callao from the 3rd. And 4 to. Primary grade, all of Public Educational Institutions. It was a comparative descriptive study. First, the reading processes in the Huancavelica and Lima-Callao groups were evaluated with the PROLEC-R (Cuetos, Rodríguez, Ruano and Arribas, 2007), finding significant differences. On that basis, the Working Memory was evaluated, with subtests of the WISC-IV Test (Wechsler Intelligence Test-2006) and the executive neuropsychological functions with some BANFE tests (Flores-Ostrosky, 2012) in both groups. The results showed significant differences in Working Memory in favor of the Lima-Callao student group. No significant differences were found in executive neuropsychological functions. Finally, no correlation was found between the processes of reading and executive neuropsychological functions. The results and their implications are discussed.